Pengaruh Overconfidence, Experienca dan Risk Perception Terhadap Pengambilan Keputusan Investasi Individu di Kota Makassar - Fahmi, Zul Fahmi -; Raprayogha, Rusdi Raprayogha (Study of Scientific and Behavioral Management, 2021)
This study aims to examine the effect of overconfidence, experience and risk perception on investment decision making. This research is a quantitative research. The population in this study were all investors in Makassar City, with a sample of 120 investors who fit the predetermined criteria. The sampling technique used in this study was non-probability sampling. The data used in this research is primary data, with the data collection method in the form of a questionnaire (questionnaire). The data analysis technique used is validity and reliability test, classical assumption test and hypothesis test using multiple linear regression analysis method. The results showed that simultaneous overconfidence, experience, and risk perception have a significant effect on investment decisions. However, partially the overconfidence variable (X1) does not have a significant effect on investment decisions (Y), while the experience variable (X2) and risk perception (X3) have a significant positive effect on investment decisions (Y).